Resuscitation in Paediatric Sepsis Using Metabolic Resuscitation–A Randomized Controlled Pilot Study in the Paediatric Intensive Care Unit (RESPOND PICU): Study Protocol and Analysis Plan - Schlapbach, Luregn J.; Gibbons, Kristen; Ridolfi, Roberta; Harley, Amanda; Cree, Michele; Long, Debbie; Buckley, David; Erickson, Simon; Festa, Marino; George, Shane; King, Megan; Singh, Puneet; et al. (Frontiers in Pediatrics, 2021)
Introduction: Septic shock remains amongst the leading causes of childhood mortality. Therapeutic options to support children with septic shock refractory to initial resuscitation with fluids and inotropes are limited. Recently, the combination of intravenous hydrocortisone with high dose ascorbic acid and thiamine (HAT therapy), postulated to reduce sepsis-related organ dysfunction, has been proposed as a safe approach with potential for mortality benefit, but randomized trials in paediatric patients are lacking. We hypothesize that protocolised early use of HAT therapy (“metabolic resuscitation”) in children with septic shock is feasible and will lead to earlier resolution of organ dysfunction. Here, we describe the protocol of the Resuscitation in Paediatric Sepsis Using Metabolic Resuscitation – A Randomized Controlled Pilot Study in the Paediatric Intensive Care Unit (RESPOND PICU). Methods and analysis: The RESPOND PICU study is an open label randomized-controlled, two-sided multicentre pilot study conducted in paediatric intensive care units (PICUs) in Australia and New Zealand. Sixty children aged between 28 days and 18 years treated with inotropes for presumed septic shock will be randomized in a 1:1 ratio to either metabolic resuscitation (1mg/kg hydrocortisone q6h, 30mg/kg ascorbic acid q6h, 4mg/kg thiamine q12h) or standard septic shock management. Main outcomes include feasibility of the study protocol and survival free of organ dysfunction censored at 28 days. The study cohort will be followed up at 28-days and 6-months post enrolment to assess neurodevelopment, quality of life and functional status. Biobanking will allow ancillary studies on sepsis biomarkers. Ethics and dissemination: The study received ethical clearance from Children’s Health Queensland Human Research Ethics Committee (HREC/18/QCHQ/49168) and commenced enrolment on June 12th, 2019. The primary study findings will be submitted for publication in a peer-reviewed journal. Trial registration number: ACTRN12619000829112